The understory fern Dicranopteris dichotoma facilitates the overstory Eucalyptus trees in subtropical plantations. Issue 5 (6th May 2014) - Wan, Songze; Zhang, Chenlu; Chen, Yuanqi; Zhao, Jie; Wang, Xiaoli; Wu, Jianping; Zhou, Lixia; Lin, Yongbiao; Liu, Zhanfeng; Fu, Shenglei
Abstract : Plant–plant interactions are important not only for understanding biodiversity maintenance and plant community assembly but also for forest conservation and management. However, our knowledge about how plant species of different functional groups interact in forests is limited. For example, understory removal is thought to enhance tree growth in subtropical plantations but such enhancement has not been experimentally confirmed. In the present study, we conducted an understory removal experiment combined with nutrient addition to examine how the understory fern Dicranopteris dichotoma interacts with overstory Eucalyptus trees and how fertilization affects that interaction in subtropical plantations. Our results demonstrate that the understory fern D. dichotoma facilitates the overstory Eucalyptus trees and that the facilitative effect is enhanced by nutrient addition. In addition to illustrating the complex interactions among plant functional groups and the importance of plant traits in predicting plant–plant interactions, our findings counter the traditional view that understory ferns primarily compete with trees for resources in subtropical Eucalyptus plantations. This information should help in the development of sustainable management practices.